GONZÁLEZ BLANCO, Azucena (ed.) (2019). Política y literatura. Nuevas perspectivas teóricas. Berlín: De Gruyter. - Jiménez Villar, Beltrán (Daimon Revista Internacional de Filosofia, 2021)
Reseña de: GONZÁLEZ BLANCO, Azucena (ed.) (2019). Política y literatura. Nuevas perspectivas teóricas. Berlín: De Gruyter.